PROGRAM KAMPUNG TANGGUH BERBASIS TEORI HIRARKI MASLOW UNTUK RECOVERY LITERASI DAN NUMERASI ANAK-ANAK PENYINTAS KEBAKARAN - Suhartini Sumadi; Kartika Tiara Syarifuddin; Adinda Shofia; Jumadiah Salsatriana; Ardawia Rumadaul; Samuel Yovel Mangando (JMM (Jurnal Masyarakat Mandiri), 2024)
Kendala yang dialami oleh anak-anak di Kota Sorong, tepatnya di Kelurahan Malabutor Distrik Sorong Manoi yang menjadi pusat kebakaran hebat yang terjadi pada tanggal 22 Maret 2023 menjadi persoalan serius, setiap anak penyintas kebakaran di daerah ini mengalami trauma hebat yang menyebabkan hilangnya minat dan semangatnya untuk belajar ke sekolah sehingga menjadi salah satu penyebab kurangnya kemampuan anak dalam bidang literasi dan numerasi. Tujuan kegiatan pengabdian ini antara lain meningkatkan pengetahuan dan keterampilan literasi dan numerasi anak, serta meningkatkan minat belajar dan mengurangi tingkat kecemasan anak. Metode pelaksanaan kegiatan pengabdian ini, yaitu kegiatan diawali dengan melakukan pre-test untuk mengetahui kemampuan awal peserta, setelah itu dilakukan implementasi kegiatan selama dua minggu dengan membagi peserta menjadi dua kelompok, yaitu kelompok jenjang dasar dan kelompok  jenjang madya sesuai dengan hasil pre-test, setelah dilakukan implementasi kegiatan selanjutnya dilakukan post-test untuk mengetahui kemampuan akhir peserta. Hasil yang telah dicapai dari kegiatan pengabdian ini, yaitu peningkatan kemampuan literasi sebanyak 85,93%, peningkatan kemampuan numerasi sebanyak 86,67%; dan peningkatan minat belajar anak sebanyak 85,75%.Abstract:  The obstacles experienced by children in Sorong City, specifically in Malabutor Village, Sorong Manoi District, which was the center of the major fire that occurred on March 22 2023, are a serious problem. Every child who survived the fire in this area experienced significant trauma, which lead to lose interest and enthusiasm to study at school. This is one of the reasons why the children in this area lack of ability in literacy and numeracy. This service project's objective to increase children's curiosity to minimize their anxiety levels alongside further developing their literacy and numerical capabilities. The method for implementing this service activity is that the activity begins by conducting a pre-test to determine the participants' initial abilities, after which the activity is implemented for two weeks by dividing the participants into two groups, namely the elementary level group and the intermediate level group according to the results of the pre-test, After implementing the activity, a post-test is then carried out to determine the final abilities of the participants. The results that have been achieved from this service activity are increasing literacy skills by 85.93%, increase in numeracy skills by 86.67%; and increasing children's interest in learning by 85.75%.Abstract:  The obstacles experienced by children in Sorong City, specifically in Malabutor Village, Sorong Manoi District, which was the center of the major fire that occurred on March 22 2023, are a serious problem. Every child who survived the fire in this area experienced significant trauma, which lead to lose interest and enthusiasm to study at school. This is one of the reasons why the children in this area lack of ability in literacy and numeracy. This service project's objective to increase children's curiosity to minimize their anxiety levels alongside further developing their literacy and numerical capabilities. The method for implementing this service activity is that the activity begins by conducting a pre-test to determine the participants' initial abilities, after which the activity is implemented for two weeks by dividing the participants into two groups, namely the elementary level group and the intermediate level group according to the results of the pre-test, After implementing the activity, a post-test is then carried out to determine the final abilities of the participantsThe method for implementing this service activity consists of: 1) FGD carried out by all 6 team members; 2) Subdistrict FKK followed by the team and head of Malabutor Subdistrict and the subdistrict employee in charge of the district where the fire occurred; 3) Program socialization, attended by the team, KKSS Secretary, IWSS representatives, literacy resource persons, residents of RW 01 village of Makassar; 4) The pre-test was attended by 37 children; 5) implementation of activities carried out for two weeks; 6) Post-test attended by 37 children; and 7) evaluation and monitoring carried out through the supervision of LP3M Education University Muhammadiyah Sorong. The results that have been achieved from this service activity are increasing literacy skills by 85.93%, increase in numeracy skills by 86.67%; and increasing children's interest in learning by 85.75%.